Sintering and crystallite growth of nanocrystalline copper doped tin oxide - Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Brito, GES; Briois, V (Amer Chemical Soc, 1999)
The effect of Cu2+ contents and of firing temperature on sintering and crystallite growth of nanocrystalline SnO2 xerogels was analyzed by thermoanalysis (mass loss (TG), linear shrinkage, and differential thermal analysis (DTA)), X-ray powder diffraction (XRPD), and EXAFS (extended X-ray absorption fine structures) measurements. Samples were prepared by two methods: (a) coprecipitation of a colloidal suspension from aqueous solution containing both Sn(IV) and Cu(II) ions and (b) grafting copper(II) species on the surface of tin pride gel. The thermoanalysis has shown that the shrinkage associated with the mass loss decreases by increasing the amount of copper. The EXAFS measurements carried out at the Cu K edge have evidenced the presence of copper in substitutional solid solution for the dried xerogel prepared with 0.7 mol % of copper, while for higher concentration of doping, copper has been observed also at the external surface of crystallites. The solid solution is metastable and copper migrates toward the surface during firing. The XRPD and DTA results have shown a recrystallization process near 320 degrees C, which leads to crystallite growth. The presence of copper segregated near the crystallite surface controls its growth.